Apllication Of The Moving Average Forecasting Method In Masonry Concrete Sales: Penerapan Metode Peramalan Moving Average Untuk Peramalan Penjualan Beton Masonry - Romi, Mochammad; Putra, Boy Isma (Procedia of Engineering and Life Science, 2024)
This study aims to create a concrete sales forecasting system using the moving average method to predict sales for the next month in order to determine the amount of production that must be supplied in the next period. The study uses the moving average method which is widely used and has accuracy in forecasting. The results obtained mean error of 32630.95, MAD of 224532, MSE of 80977550000, standard error of 318154, Mape of 12.621% and average forecast of 1960074.0. The study implies that the moving average method is an effective tool for sales forecasting and can be used to make informed decisions about production planning and estimating future growth Highlight : The study aims to create a concrete sales forecasting system using the moving average method. The moving average method is an effective tool for sales forecasting and can be used to make informed decisions about production planning and estimating future growth. The study provides statistical measures such as mean error, MAD, MSE, standard error, and MAPE to evaluate the accuracy of the moving average method. Keywords: Sales forecasting, Moving average method, Production planning, Accuracy, Informed decisions.